Threshold photoelectron spectroscopy of 9-methyladenine: theory and experiment. Issue 6 (22nd October 2021) - Laamiri, K.; Garcia, G. A.; Nahon, L.; Ben Houria, A.; Feifel, R.; Hochlaf, M.
Abstract : TPES spectroscopy is used to unveil the complex vibronic structure of 9-methyladenine cations. Abstract : We present a combined experimental and theoretical study of single-photon ionization of 9-methyladenine (9MA) in the gas phase. In addition to tautomerism, several rotamers due to the rotation of the methyl group may exist. Computations show, however, that solely one rotamer contributes because of low population in the molecular beam and/or unfavorable Franck–Condon factors upon ionization. Experimentally, we used VUV radiation available at the DESIRS beamline of the synchrotron radiation facility SOLEIL to record the threshold photoelectron spectrum of this molecule between 8 and 11 eV. This spectrum consists of a well-resolved band assigned mainly to vibronic levels of the D0 cationic state, plus a contribution from the D1 state, and two large bands corresponding to the D1, D2 and D3 electronically excited states. The adiabatic ionization energy of 9MA is measured at 8.097 ± 0.005 eV in close agreement with the computed value using the explicitly correlated coupled cluster approach including core valence, scalar relativistic and zero-point vibrational energy corrections. This work sheds light on the complex pattern of the lowest doublet electronic states of 9MA + . The comparison to canonical adenine reveals that methylation induces further electronic structure complication that may be important to understand the effects of ionizing radiation and the charge distribution in these biological entities at different time scales.